Pengaruh Gaya Kepemimpinan, Budaya Organisasi, dan Pengembangan Karyawan terhadap Kinerja - Rahmisyari, Rahmisyari (Jurnal Aplikasi Manajemen, 2011)
Objective in this study is to found out about leadership style, organizational culture, and employees' development toward industrial performance of Bosowa Maros cement in South Sulawesi. Sample - collection in this study consists of 266 employee of cement industry of Bosowa Maros in South Sulawesi. Data collection technique is by using interview with questionnaire model and observation technique. Result of this study has proved that leadership style significant effect toward organizational culture with coefficient value of 0.908. Leadership style also significant influence toward employee development with coefficient value of 0.398. Organizational culture has significant effect on employee development with coefficient value of 0.952. Leadership style significant effect toward performance with and coefficient value of 0.250. Organizational culture has insignificant effect toward performance with and coefficient value of 0.174, it showed that organizational culture has indirect contribution toward performance. It is seen from analysis result showed that organizational culture has indirect effect toward performance through employee development with coefficient value of 0.774. Employee development has significant effect toward performance with coefficient value of 0.250.